Patient Satisfaction Level at the Outpatient in University of Muhammadiyah Malang Hospital - Faqih Ruhyanudin; Miftachul Zanah; Sunardi Sunardi; Zahid Fikri (Jurnal Keperawatan, 2022)
Introduction: The hospital is one of the health care facilities expected to provide appropriate health services and information for patients and the broader community. Patient satisfaction is one of the essential things for health care providers as a measuring tool to evaluate service quality. Satisfaction can increase the number of visits that impact increasing sources of income for hospitals and, at the same time, realize a healthy and prosperous society. Objectives: The purpose of this study was to identify patient satisfaction in the outpatient installation of the Muhammadiyah Malang University Hospital in indicators of conformity with expectations, ease of obtaining services, and willingness to recommend. Methods: The design of this research is descriptive observational. The sample in this study were patients who visited the outpatient installation of the University of Muhammadiyah Malang Hospital in November 2020; as many as 136 respondents were selected by accidental sampling. Data collection with a patient satisfaction questionnaire. Data analysis with descriptive analysis and presented in the frequency distribution. Results: The results showed that as many as 68.4% of respondents stated that the service was as expected, 52.2% were easy to access services, 50.7% were willing to recommend to other parties, and 54.4% said they were satisfied. Conclusions: Patient satisfaction with the University of Muhammadiyah Malang Hospital in several indicators is relatively high, but it needs improvement in several respects. Nurses, doctors, and other human resources need to maintain good service delivery by providing appropriate, fast, always smiling, and friendly service to patients.